Effects of Online Learning Instruction and Blended Instruction on Academic Performance and Digital Literacy of Pre-Service Teachers in an Educational Technology Course - Onwuagboke, Bede Blaise Chukwunyere; Nwakamma, Christiana Onyejuru; Umune, Hope Chinyere (Darul Yasin Al Sys, 2025)
This study examined the effects of fully online teaching and a blended teaching approach on the academic performance and digital literacy skills of student-teachers enrolled in an Educational Technology course at Alvan Ikoku Federal University of Education, Owerri. A quasi-experimental pre-test–post-test design was adopted, with a population of 589 level 200 pre-service teachers from the Faculty of Social and Management Sciences. The sample consisted of 92 student-teachers drawn from two intact groups in the Economics and Social Studies departments, taught during the second semester of the 2023/2024 academic year. Data were collected using two researcher-developed instruments: the Educational Technology Achievement Test (ETAT) and the Digital Literacy Skills Scale (DLSS), both validated by experts. Reliability testing yielded coefficients of 0.85 for ETAT (Kuder-Richardson 20) and 0.81 for DLSS (Cronbach’s alpha). Descriptive statistics (mean and standard deviation) were used to address research questions, while analysis of covariance (ANCOVA) tested the hypotheses. Findings showed that both groups achieved substantial learning gains, with the blended learning group outperforming the online-only group in academic performance. Additionally, both groups demonstrated improved digital literacy skills. The study concludes that blended learning offers greater instructional benefits and recommends that educational technology lecturers incorporate online delivery into regular face-to-face teaching to optimize learning outcomes.